Catalytic and inhibitory roles of K and Ca in the pyrolysis and CO2 or steam gasification of Erianthus, and their effects on co-gasification performance. (November 2021) - Koido, Kenji; Kurosawa, Kakeru; Endo, Kenji; Sato, Michio
Abstract: Increasing biomass demand for domestic power production due to feed-in tariffs has led to the use of herbaceous perennial energy crops such as Erianthus arundinaceus (Erianthus) as a biomass resource. Erianthus (JES1) is obtained in a yield of approximately 14 t/ha on a dry basis in Nasu-shiobara, a temperate climate region of Japan and its standing-dead characteristics permit a small drying cost. In this study, the catalytic roles of Ca and K on the CO2 and steam gasification of Erianthus char were investigated using thermogravimetry-differential thermal analysis (TG-DTA), and the effect of blending Erianthus with timber waste on the co-gasification performance was elucidated. The obtained results showed that the loading of K into the demineralised char (DC) enhanced both the CO2 and steam gasification processes. In contrast, the loading of Ca on DC slightly inhibited CO2 gasification, while steam gasification was significantly inhibited. In the co-gasification of an Erianthus-blended timber waste feedstock, the conversion to gas and cold-gas efficiency was promoted in the case of an Erianthus blend ≤30% due to the presence of inorganic components, such as K, in the blended feedstock. Graphical abstract: Image 1 Highlights: Effects of Ca and K contents on Erianthus CO2 /steam gasification were investigated. CO2 /steam gasification was accelerated by K and inhibited by Ca addition. Enhanced co-gasification of timber waste was observed with ≤30% Erianthus addition.